Avifaunal Diversity of Institute of Forestry Complex, Hetauda Metropolis, Nepal - Bajagain, Santosh; Pokhrel, Santosh; Baniya, Shishila; Pradhan, Aavas; Paudel, Surakchya; Joshi, Ishwar Datt (FORESTRY: Journal of Institute of Forestry, Nepal, 2020)
Avifaunal diversity is the measure of species diversity via species richness and evenness. To this aim, avifaunal survey was conducted in the Institute of Forestry Complex, Hetauda from November 2017 to June 2018. Using line transect and point count methods, 132 species of birds were recorded, representing 15 orders and 44 families. Three species of these birds are in IUCN Red List while 90, 27 and 15 species are residential, visitor and migrant respectively. Higher Shannon diversity index (4.47) and Margalef index (18.78) indicate marked diversity and richness of bird species. A high value calculated for the Simpson index (0.98) represents higher evenness within the species individuals. Although, Pielou’s evenness index (0.92) shows uniformity in the species distribution, Shannon index seems to be influenced by diversity index, species richness and evenness values. The avifaunal diversity in the study area shows the importance of the Institute of Forestry Complex as a suitable bird habitat.